Validity and Practicality of Learning Model Development of LAPS-Heuristics with Local Wisdom on Students’ Metacognitive Ability - asfar, andi muhammad irfan taufan; Asfar, Andi Muhamad Iqbal Akbar; Trisnowali, Andi; Dahlan, Jarnawi Afgani; Prabawanto, Sufyani; Nurannisa, Andi (Jurnal Penelitian dan Pengembangan Pendidikan, 2022)
Metacognition is one of the skills needed in a competitive era because it involves cognitive processes in communication, attention, memory, and processing and using information. However, the facts show that students' metacognitive abilities still need to improve. The overcome the low ability of metacognition, local wisdom-based learning is an alternative solution. This study aims to develop and test the feasibility level of the LAPS-Heuristics learning model with local wisdom on students' metacognitive abilities. This type of research uses research & development modified by Borg and Gall with three stages: preliminary studies, model trials, and model experiments. As for the research subject, the student of class IX at SMP Negeri 1 Kahu. The instruments used in the research include observation, interviews, validation, and practicality questionnaires. The results showed that the LAPS-Heuristics learning model developed with local wisdom was valid and practically applied in the learning process with an average score of 3.5 or a percentage of 92% so that the LAPS-Heuristics learning model with local wisdom can be implemented in the learning process to overcome the low metacognitive ability of students.